2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944351
|View full text |Cite
|
Sign up to set email alerts
|

Sternal pulse rate variability compared with heart rate variabilit on healthy subjects

Abstract: The heart rate variability (HRV) is a commonly used method to quantify the sympathetic and the parasympathetic modulation of the heart rate. HRV is mainly conducted on electrocardiograms (ECG). However, the use of photo-plethysmography (PPG) as a marker of the autonomic tone is emerging. In this study we investigated the feasibility of deriving pulse rate variability (PRV) using PPG signals recorded by a reflectance PPG sensor attached to the chest bone (sternum) and comparing it to HRV. The recordings were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…19 In contrast to the many negative results reported during intense exercise, there are other researchers who reported an overall stronger agreement. 49 Also, some other research groups reported that PPG yielded higher HRV values. 36 However, all these studies involved only a sample size of few subjects.…”
Section: Exercisementioning
confidence: 96%
“…19 In contrast to the many negative results reported during intense exercise, there are other researchers who reported an overall stronger agreement. 49 Also, some other research groups reported that PPG yielded higher HRV values. 36 However, all these studies involved only a sample size of few subjects.…”
Section: Exercisementioning
confidence: 96%
“…Reflection mode allows measurements from multiple locations on the body while the backscattered light intensity might be significantly lower in comparison with transmission mode measurements. In recent years, several locations for PPG sensors have been explored, such as finger (Rhee et al 2001), forehead (Peralta et al 2017), earlobe (Lu et al 2009, Vescio et al 2018, wrist (Grajales et al 2006, Salehizadeh et al 2015, chest (Chreiteh et al 2014) or abdomen (Spigulis et al 2005). Wearable pulse rate sensors based on PPG signals have become popular for instantaneous assessment of pulse rate (Tamura et al 2014, Zhang et al 2014.…”
mentioning
confidence: 99%
“…First of all, a probe placed at the sternum is less obtrusive than earlobe or finger probes. Secondly, the sternum can be used to monitor other clinically relevant parameter such as pulse wave variability [10] and pulse oximetry [11]. Respiratory pressure variations in the thoracic cavity affects the blood volume on the venous side and on the arterial side.…”
Section: Discussionmentioning
confidence: 99%